Analysis of Preferences in Choosing Upper Secondary Schools Among Private MTs Students Using a Multinomial Logistic Regression Model - Besse Arnawisuda Ningsi; Sarah Febriyani; Irvana Arofah (PT. BATARI EDU CALYA, 2026)
For MTs students, the selection of higher secondary school (SMA, SMK and MA) is a considerable decision that can be affected by a combination of several academic and non-academic aspect. The purpose of this study is to find out the determinants of higher educational choices in Private MTs students. The analysis method used is multinomial logistic regression to determine the factors that influence the choice of Private MTs students in Pinang District, Tangerang City with a sample of 226 students. Based on the results of the analysis, there is one variable that influences the selection of a top-level advanced school for Private MTs students in Pinang District, Tangerang City, which is tuition fees (P-value < 0.05). Tuition fees affect students' choice between high school and vocational school, and other variables do not show statistically significant effects.